Potential contribution of CD-ROM technology to libraries of educational institutions in Malaysia - Wan Dollah, Wan Ab Kadir (University of Malaya Library, 1995)
In this article the author attempts to clarify the concept of CD-ROM. CD-ROM as an optical information system is not only capable of extending the scope of information in the library, but it can also be regarded as a teaching and learning tool based on sophisticated technology. The author discusses some learning characteristics of CD-ROM and how this technology can be utilised. The article also outlines the management implications when this technology is being introduced.